2018
DOI: 10.1002/anie.201808551
|View full text |Cite|
|
Sign up to set email alerts
|

Digging the Sigma‐Hole of Organoantimony Lewis Acids by Oxidation

Abstract: The development of group 15 Lewis acids is an area of active investigation that has led to numerous advances in anion sensing and catalysis. While phosphorus has drawn considerable attention, emerging research shows that organoantimony(III) reagents may also act as potent Lewis acids. Comparison of the properties of SbPh , Sb(C F ) , and SbAr with those of their tetrachlorocatecholate analogues SbPh Cat, Sb(C F ) Cat, and SbAr Cat (Cat=o-O C Cl , Ar =3,5-(CF ) C H ) demonstrates that the Lewis acidity of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 74 publications
2
95
0
2
Order By: Relevance
“…Shortly after, Gabbaï and colleagues compared the catalytic activities of antimony(III) and antimony(V) compounds in different transformations . Oxidation results in a deeper σ‐hole and an increased catalytic activity can be expected.…”
Section: Pnictogen Bondingmentioning
confidence: 99%
“…Shortly after, Gabbaï and colleagues compared the catalytic activities of antimony(III) and antimony(V) compounds in different transformations . Oxidation results in a deeper σ‐hole and an increased catalytic activity can be expected.…”
Section: Pnictogen Bondingmentioning
confidence: 99%
“…In a recent study, Matile and co-workers showed that SbPh(C 6 F 5 ) 2 is an active chloride anion transporter that interacts with the anion via pnictogen-bonding. 24 Based on the understanding that such interactions are greatly strengthened by oxidation of the antimony center, 28,29 our group concomitantly introduced a family of stibonium cations (C) 30,31 whose anion transport activity is controlled both by the Lewis acidity of the antimony centre and the lipophilic exterior projected by the aryl substituents. 25 Our interest in main group-based anion receptors 32,33 has also led us to consider the use of sulfonium cations for anion capture via chalcogen-bonding, [34][35][36] as in the case of D which forms an isolable uoride anion complex.…”
Section: Introductionmentioning
confidence: 99%
“…While most of these compounds have been described previously, [3c, 4c, 13] 6 was prepared by reaction of 3 with o-chloranil and its structure was verified by X-ray crystallography. [14] We note in passing that the use of the electron deficient tetrachlorocatecholate ligands in 5 and 6 is necessary to stabilize the + Voxidation state of these compounds. With these compounds at our disposal, we decided to test their reactivity toward simple Lewis bases.For the purpose of this study,w ec hose to benchmark the Lewis acidity of these compounds against triphenylphosphine oxide,abase known to coordinate to antimony(V) compounds.…”
mentioning
confidence: 99%
“…Addition of stibine 2 or 3 to as olution of Ph 3 PO in hexanes triggers ad ownfield shift of the 31 PNMR signal from 23.4 to 28.5 ppm in the case of 2 and 28.4 ppm in the case of 3.C rystals of Ph 3 PO!Sb(C 6 F 5 ) 3 were obtained by cooling apetroleum ether (40-60) solution to À20 8 8C, confirming the molecular structure of the proposed adduct. [14] The X-ray crystal structure of Ph 3 PO!Sb(C 6 F 5 ) 3 illustrates the presence of an…”
mentioning
confidence: 99%